Productivity Evaluation and Tuber Characterization of Some Potato Cultivars in Turkey - Yusufoğlu, İbrahim; Akıncı, Sermin; AL Hajhamed, Abdulsalam (Journal of agricultural, environmental and veterinary sciences, 2021)
The main objective of this study was to evaluate the productivity and physical characterization of tubers of fifteen potato cultivars grown under greenhouse conditions during 2019 and 2020. The highest plant productivity was 258.1 g in Universa cultivar, the lowest was 125.6 g in Triomphe. The highest number of tubers per plant was 10.00 tubers in Melody, the lowest was only 3.00 tubers in Aurea. The average of tuber weight ranged between 17.80 g as a minimum weight in L.Olympia and 59.95 g as a maximum significant weight in Aurea, which outnumbered all studied cultivars. The Tuber Specific Gravity (SG) ranged between 1.067 in passion and 1.211 in Triomphe. The highest number of eyes per tuber was 12.13 in Universa the lowest was 4.25 in Melody. Shallow eye depth was observed in most cultivars, meanwhile deep eyes were only in Aurea and Christal cultivars. The tubers shape was long in Passion, Diego, Soleia, L. Olympia, and Universa. it was oval in Melody, Husar, Malice, Aurea, Triomphe, Alonso and Blondine. On the other hand, the shape of tubers in both Christal and Galata was round. Many important correlation coefficient relationships were observed between traits, a significantly positive correlation coefficient between stems numbers and tubers number per plant, number of tubers per plant and plant productivity, plant height and number of tubers per plant. Meanwhile, significantly negative correlation coefficient was noted between number of tubers per plant and average of tuber weight, number of stems per plant and average of tuber weight, plant productivity and SG of tubers. Overall results of this study suggest that there is a big differentiation among potato genotypes which led to farther productivity and physical characteristics can be improved for having most suitable and adaptable potato cultivars in Turkey.
Keywords: Potato cultivars; Solanum tuberosum; productivity; evaluation; tuber; Turkey